MEASURING WIND RESOURCES - Igrec, Dalibor; Chowdhury, Amor; Hadžiselimović, Miralem; Štumberger, Bojan (Journal of Energy Technology, 2024)
Starting a wind farm, like starting any other business, requires a significant amount of research, start-up capital, and development before the first turbine begins to spin. If we know what to expect before we begin, the project will run more smoothly. Specialized services of consultants, contractors, and legal representatives are necessary to avoid problems that could end the operation before it starts. Professional wind measurement, and its accuracy and reliability are thus very important in predicting economic viability before starting a wind farm (projecting), as well as in monitoring already-installed wind farms (verifying).Even a small change in the wind speed in a particular area can significantly affect the power yield efficiency of the wind turbine. Therefore, for the prospective development of a wind turbine, it is important to consider the wind resources and information on how regularly the wind blows, the direction of the wind, variations in wind speed and so on. On the basis of this information, performance control mechanisms are integrated in the wind turbine. Before the installation of a wind farm, analyzing the space professionally is recommended. The collected meteorological data should accurately describe the wind potential of the space. This is why the measuring systems should meet the highest quality demands in terms of accuracy and reliability. We have therefore decided to develop system equipment for measuring wind resources. Thispaper describes the basic properties of the measurement technique and our approach for measurements, data collection, and data mining.